Bidirectional relationship between serum creatinine to cystatin C ratio and chronic kidney disease: a mediation analysis of depression in a national aging cohort - Cai, Qiong; Zhong, Qing; Ali, Sajid; Yang, Wenting; Chen, Yanan; Ao, Bo; Huang, Youliang (Frontiers in psychiatry, 2025)
CCR is an emerging biomarker for renal function, yet its relationship with depression and CKD risk has not been confirmed and is understudied in the population. This study aimed to investigate the association between CCR and CKD, as well as all-cause mortality, among middle-aged and elderly Chinese individuals. Additionally, it sought to explore the bidirectional mediating effect of depression in the association of CCR with CKD. This study analyzed participant data from the China Health and Retirement Longitudinal Study(CHARLS) from 2011 to 2020. The 10-item Center for Epidemiological Survey Depression Scale(CES-D-10) was used to assess depressive symptoms. Kaplan-Meier survival analyses were used to generate survival curves for participants stratified by different levels of CCR. Multivariate logistic regression was employed to examine the CCR-CKD, CCR-depression, and CKD-depression association. Multivariate Cox regression assessed the association between CCR and all-cause mortality. The potential mediating effect of depression between CCR and CKD was determined by bidirectional mediation analysis. The study included a total of 6,243 participants, comprising 2,835 men and 3,408 women. Multivariate logistic regression analysis revealed that CCR was positively correlated with an increased risk of CKD( ) and negatively correlated with the severity of depression( ). Higher CCR levels correlated with lower all-cause mortality( ). Depression had a partial negative mediating effect in the association between CCR and CKD. Restricted cubic spline curves showed a U-shaped, nonlinear association between CCR and all-cause mortality. Higher levels of CCR are associated with a higher risk of CKD and with lower all-cause mortality, and CCR could be a biomarker for early diagnosis of CKD. Depression may have a negative effect on the association of CKD and CCR, suggesting that CCR has an underestimated risk for predicting and recognizing CKD in depressed populations. Mental health factors are important in risk prediction and comprehensive management of CKD.